Behavior of Rubberized Reinforced Concrete Columns under Axial Loading - Ahmed Arafa; norhan yousef; Omar Ahmed Farghal; Atef Hassanein (JES: Journal of Engineering Sciences)
Utilizing waste rubber in concrete enhances its ductility, toughness, and impact resistance while reducing the structural members' weight. Additionally, incorporating waste rubber supports the creation of environmentally friendly concrete and promotes sustainable production, which is increasingly emphasized nowadays. This research examines the behavior of full-scale rubberized reinforced concrete (RC) columns under concentric loading. Eight reinforced concrete columns with dimensions of 300×300×1200 mm were constructed and subjected to concentric loading until failure. The primary variables in this study were concrete type and stirrup configuration, and spacing. Two columns, cast with normal concrete, served as references for comparison with six rubberized RC columns. The rubberized concrete mix had crumb rubber (CR) at 20% volume substitution for sand, ensuring admissible fresh properties and minimal strength depletion. Key design considerations, including damage progression, ultimate strength, ductility, and toughness, were analyzed. The findings indicate that rubberized concrete can achieve comparable performance to traditional concrete, with improvements in ductility. An increase in strength and ductility were recorded for the concrete cores of well-confined columns.